Nanofósseis Calcários Quaternários da Bacia de Campos, Brasil Sistemática e Diagênese Primária - TOLEDO, FELIPE ANTÔNIO DE LIMA; GONÇALVES, HELENA MARIA SOUTO; COSTA, KAREN BADARACO (Pesquisas em Geociências, 2002)
<!– .p text-align: justify; –> The analyses of five piston cores (SG91-09/PC-01, SG91-14/PC-04, SG91-14/PC-06, SG91-14/PC08 e SG91- 14/PC09) sampled on Campos Basin - RJ, Brazil, permitted the systematic studies in Quaternary calcareous nannofossils and the description of the primary diagenesis effects on this microfossils using optical microscope and scanning electron microscope. The observation of “in situ” dissolution and reprecipitation of calcium carbonate recorded limitate the systematic studies of calcareous nannofossils and show the importance to use both optical and scaning microscope.